An Overview Of Virtual Reality-Based Educational Animation Design Optimisation - Liew, Nyet Fong; Terry, Lucas (UNIMAS Publisher, 2025)
Designing virtual reality (VR) experiences for tertiary education appropriately remains an active research topic. VR-based educational animation is seen as a low-cost VR option. It has been mentioned that more effort should be put into designing educational content and the role of design elements for VR. This thematic paper aims to explain the current research in VR-based educational animation. There have been efforts to propose strategies for collaboration with animators, improving the video quality, testing the effects of informational elements, and deriving design guidelines to enhance the video design. The overview identified loopholes and gaps, i.e., a lack of information about learners’ preferences for design elements and how to utilise the design elements better. The paper that investigates animators’ VR-based educational animation design experience is scarce. Hence, future research could investigate and fill in the gaps mentioned, which includes providing a clear description of the VR-based video design. It is hoped that this thematic paper can support and provide insights into future instructional design and development of VR-based educational animation, thus aiding its wider educational adoption.